Sustainable Amazonian landscapes - International Center for Tropical Agriculture (2015)
Peru and Colombia, which encompass 23% of the Amazon rainforest, are committed to reducing net losses of their natural forests to zero as well as to designing national action plans for mitigating and adapting to climate change. In order for the two countries to meet these commitments, they urgently need to identify agricultural systems of proven effectiveness for increasing carbon sinks, protecting endangered forests, enhancing the adaptation capacity of local communities to climate change, and improving agricultural productivity.